Evaluation of Violence Prevention Programs in Four New York City Middle Schools, 1993-1994 - Bannister, Tanya ([Verlag nicht ermittelbar], 1999)
This research project sought to evaluate the impact of broad-based multifaceted violence prevention programs versus programs that have a more limited focus. Two specific programs were evaluated in four New York City middle schools. The more limited program used Project S.T.O.P.(Students Teaching Options for Peace), a conflict resolution and peer mediation training program. The full multi-faceted program combined Project S.T.O.P. with Safe Harbor, a program that provided victimization counseling and taught violence prevention. The effects of this combined program, offered in three of the middle schools, were compared to those of just the Project S.T.O.P. program alone in one middle school. To study the program models, researchers used a quasi-experimental pre-post design, with nonequivalent comparison groups. Questionnaires were given to students to assess the impact of the two programs. Students were asked about their knowledge and use of prevention programs in their schools. Data were also collected on students' history of victimization, such as whether they were ever attacked at school, stolen from, mugged, or threatened with a weapon. Students were also asked about their attitudes toward verbal abuse, victims of violence, and conditions when revenge is acceptable, and their exposure to violence, including whether they knew anyone who was sexually abused, beaten, or attacked because of race, gender, or sexual orientation. Additional questions covered students' use of aggressive behaviors, such as whether they had threatened someone with a weapon or had beaten, slapped, hit, or kicked someone. Data were also gathered on the accessibility of alcohol, various drugs, weapons, and stolen property. Demographic variables include students' school grade, class, sex, number of brothers and sisters, and household composition.